Clinical Strategies to Enhance Fluency Maintenance in Adults and Adolescents who Stutter. (30th June 2015) - Block, S.; Carey, B.
Abstract: This seminar will combine several themes or topics of the conference: effectiveness and efficacy of therapy, stuttering in adults and technology in practice. It will have a focus on innovative practice including stand-alone treatment, application of technologies, incorporation of self-help groups and self-management. Fluency maintenance and relapse are issues most speech therapists have to routinely manage during the long-term treatment process. However, in spite of outcome research showing the very real need for relapse prevention and relapse management and theoretical recommendations, clinicians often have to draw on their own experiences about how and when to implement relapse prevention strategies. This presentation helps clinicians to develop client focussed relapse prevention and/or relapse management strategies by drawing on relevant research outcomes, the clinical experience of the presenters as stuttering treatment specialists, and those of other participants.Craig (2010) confirms the importance of generalizing fluency skills and offering anti-relapse therapy following initial treatment (p.214). Indeed, most programs and research trials include recommendations for a focus on relapse or maintenance, but few provide the clinical strategies with which to do this. Maintenance and relapse management require specific clinical skills and careful monitoring, by both the clinician and the client. This seminar/workshop will draw on evidence for managing stuttering across the lifespan. It will address strategies to manage fluency maintenance to enhance treatment outcome. In particular, it will also address a variety of ways of facilitating fluency following relapse in adolescents and adults who stutter. Participants will have the opportunity to discuss their own and some set clinical scenarios. Video examples will be provided indicating problems identified by clients who have presented for relapse management. Participants will engage in problem-solving a wide range of issues that can cause relapse. There will be opportunities to discuss and set realistic goals, from several perspectives. A range of treatment strategies will be identified and the merits of each will be discussed. Incorporation of recent findings regarding anxiety and mood disorders will be presented (e.g. Iverach, Jones et al., 2009; Iverach, O-Brian et al., 2009). The inclusion of telehealth as a practical option (Carey et al., 2009 ) will be discussed, to increase service options. The proposers of the seminar are both experienced speech therapists and clinical educators with many years of experience treating adults and adolescents who stutter. They propose a flexible opportunity to interact with clinical scenarios and problem solve in small groups, whilst incorporating current research findings.